Performance evaluations and employee turnover intentions: Empirical evidence from linked employer–employee data - Laura Pohlan; Susanne Steffes (Industrial Relations: A Journal of Economy and Society, 2024)
In this article, we study whether performance evaluations can serve as an instrument for firms to increase employee retention. Feedback on one's own performance may affect individual turnover intentions differently depending on the relative wage rank of workers among their peers. In line with these considerations, empirical evidence based on panel employer–employee data shows that relatively low-paid employees decrease their turnover intentions after the implementation of a performance evaluation system at the establishment level. We find no effect for relatively high-paid employees.
Keywords: 330